A Decolonial Spinoza: An Interpretation in Tension - Emerson Bodde (Journal of Spinoza Studies)
Following Santiago Slabodsky’s articulation of a tradition of decolonial Judaism and his suggestion that Spinoza might be considered a part of it, I argue that Spinoza may be considered a decolonial thinker. While outlining the historical context in which the Jewish Spinoza wrote, I present an interpretation of Spinoza’s philosophy—in particular, the political implications of his substance monism and naturalism—and demonstrate how it satisfies general standards for a decolonial theory. In addition to highlighting relevant topics in Spinoza’s corpus, including the notion of servitude and his passing comments on Islam, I rebut several potential objections to this reading. While accepting points of tension, I claim a generally consistent, decolonial character may define the overall system of Spinoza’s philosophy. I conclude the paper by considering the relationship between this interpretation and the only proper mention of colonialism in Spinoza’s corpus, i.e., his waking dream of a silent Afro-Brazilian man.